Sistem Pendeteksi Keamanan Ruangan “Smart Security” Dengan Metode Fuzzy Logic Menggunakan Sensor PIR Berbasis Internet of Things (IoT) - Rima Tamara Aldisa; Sechan Alfarisi (STMIK Budi Darma, 2022)
The system is an attempt to assist in detection using sensors, an effort made for a room or house if people come or enter. A tool is designed that can be easy, affordable and can be used to prevent the danger of unknown people from entering the room or even into our homes. The author designed a